Coinfection of COVID-19 and Dengue: A Case Report - Prapty, Chowdhury Nusaiba Binte Sayed; Ahmed, Nafisa; Araf, Yusha; Yang, Zhijun; Zhai, Jingbo; Hosen, Mohammad Jakir; Zheng, Chunfu (Frontiers in Medicine, 2022)
While the COVID-19 pandemic takes the world by storm, dengue-endemic regions are in danger of developing a co-epidemic in the form of COVID-19/dengue coinfection. With both infections as causes of high morbidity rates, the potentially fatal outcomes of coinfection are even greater, and several cases are emerging, severe and moderate, showing how common it may become in certain regions. The case reported here shows a 38-year-old male patient with high-grade fever, with complaints of nausea, joint, and muscle aches, all characteristic symptoms of COVID-19 and dengue. Initially suspected of being infected with COVID-19 only, the RT-PCR test of the nasopharyngeal swab confirmed COVID-19 infection while the positive reactivity to IgG and IgM in the Dengue Duo test revealed a dengue coinfection. Except for the persistent high fever, the patient's symptoms were not very severe, to begin with, although the tests did confirm the infections to be "moderate to severe" and showed steady and rapid recovery. The tests showed some interesting results, which provided additional research opportunities. Overall, this case report illustrates the existence of coinfections in the Philippines, demonstrating the difficulty in distinguishing the two infections and the need for proper diagnosis, prevention, and management measures.